Early medieval garnet-inlaid metalwork: a comparative analysis of disc brooches from early Wessex - Hamerow, H; Shortland, A; Cameron, E (Cambridge University Press, 2020)
Garnet-inlaid metalwork was an emblem of elite culture in the early medieval North Sea world. This study compares three Anglo-Saxon garnet-inlaid brooches that are exceptionally similar in design and appearance. All three date to the seventh century, a period that saw the emergence of leading families that used such deluxe dress items to enhance their political position. The central hypothesis explored here is that the brooches were produced by the same, or by closely linked, goldsmiths working under the patronage of such a family. Integrated analysis was conducted using microscopy, CT scans, XRF and XRD, in part to establish whether the garnets used came from the same or different sources.